The globalization of Malaysian cinema : a study on feminism as a construction of urban culture in Gol & Gincu / Ayu Haswida Abu Bakar - Abu Bakar, Ayu Haswida (UPENA, 2006)
This essay looks at the representation of gender in order to examine the element of feminism inherent in the contemporary Malaysian film, Gol & Gincu (2005) directed by Bernard Chauly. The essay argues that the strong theme of feminism embedded in the film is a result of urban culture which is the direct product of globalization.